Connecting to nature through community engaged scholarship: Community gardens as sites for collaborative relationships, psychological, and physiological wellbeing - Ward, Kumara San; Truong, Son; Gray, Tonia (Frontiers in Psychiatry, 2022)
Community gardens are recognised as being associated with a range of benefits for participants that include enhanced outcomes in physical and affective domains and community building. The purpose of this study was to research the impact of the New South Wales Royal Botanic Gardens (RBG) Community Greening (CG) program and to inform the ongoing development of this community outreach program. The organic community partnerships inherent in the design and the relationships between the Community Greening program participants and researchers is examined through the lens of Community Engaged Scholarship (CES). Over a seven-month period, the CG team implemented a community garden development program in six sites. Mixed-method research on the impact of the program found that the community gardening participants experienced positive changes in physical activity, psychological wellbeing and motivation for social engagement, and these outcomes were facilitated as a result of their relationships with members of the CG team. This paper examines how such programs, when explicitly framed as CES, could assist in consolidating nature-based community health and wellbeing programs and further legitimise community partnerships in development of community garden and green spaces as academically sound investigation and socio-economically justified activity. Expansion of this nature-based collaboration model may also enhance community engagement in green exercise, psychological wellbeing and community cohesion, and in turn support advocacy for greener environments locally, regionally and nationally.